Are we ready to consider transgenerational epigenetic effects in human health risk assessment?. (21st November 2013) - Alyea, Rebecca A.; Gollapudi, B. Bhaskar; Rasoulpour, Reza J.; O'Hagan, Heather; Tang, Winnie
<x xml:space="preserve">Abstract</x> Recently, there has been a growing concern that chemically or nutritionally mediated epigenetic changes might lead to adverse health outcomes. The natural question is whether the existing chemical safety assessment paradigm is or is not protective of epigenetic‐mediated effects, and if there is a need to incorporate new endpoints to specifically address epigenetics. Of particular interest are transgenerational epigenetic effects, which can be passed on through multiple generations. To investigate these questions, a comparison was performed between OECD guideline rat toxicology studies versus several rat transgenerational epigenetic studies. This analysis focused on vinclozolin owing to the availability of a comprehensive suite of dose‐response data (NOAEL, reference dose, and human exposure estimates) for both conventional and epigenetic endpoints. This analysis revealed that vinclozolin transgenerational effects were demonstrated at a dose level (100 mg/kg/day) that was: (1) ∼40‐fold higher than the overall lowest‐observed‐adverse‐effect level (LOAEL) from rat guideline studies, (2) ∼80‐fold higher than the lowest NOAEL from rat guideline studies, (3) ∼80, 000‐fold higher than the reference dose for the molecule, and (4) ∼1.2‐million fold above human exposure estimates. Through this analysis, we conclude that additional research across a spectrum of doses is necessary to elucidate the interplay between epigenetics and apical endpoints before considering epigenetics in human health risk assessment. Therefore, we recommend focusing future research toward (1) examining for potential causal relationships between epigenetic alterations and adverse apical endpoints, and (2) understanding the dose‐response relationship of these causal epigenetic alterations when compared with those of the apical endpoints. Environ. Mol. Mutagen. 55:292–298, 2014. © 2013 Wiley Periodicals, Inc.